Development of a Sense of Humor in Preschoolers and Younger Schoolchildren: a Review of Diagnostic Tools - Arina N. Shatskaya; Ekaterina S. Oshchepkova; Nikolay E. Veraksa; Larisa F. Bayanova; Maria S. Kovyazina (Национальный психологический журнал)
Background. A sense of humor is one of the most productive coping strategies that allow both adults and children to effectively cope with stress, regulate emotions, and establish positive social interactions with others. The study of adaptive capabilities of a developed sense of humor, as well as its relationship with various aspects of mental development is limited due to various methodological limitations of existing methods of diagnosing the sense of humor and related constructs (irony, sarcasm, sense of the comic). Objectives. The purpose of the current paper is to present the results of a review of the main types of diagnostic tools for assessing the development of a sense of humor in preschoolers and younger schoolchildren 4–10 years old in Russian and foreign studies over the last thirty years. Study Materials. A literature search retrieved 966 publications (626 English-language publications and 340 Russian-language ones). After applying study selection criteria, 66 publications were included in the final qualitative analysis. Methods. The diagnostic tools used in the reviewed publications were divided into six types according to the main content of the used method of diagnosing the sense of humor. A description of the procedures of the selected types of techniques, as well as the conditions of applicability of each of them, is given. Results. The results of the conducted review allow us to divide the whole diagnostic toolkit for assessing the sense of humor of preschoolers and younger schoolchildren into techniques for assessing understanding and creation of humor. The most important limitations of each type of methods and recommendations for their use are given. The materials of this review may be useful in selecting diagnostic tools in studies of the sense of humor in children aged 4–10, as well as in developing new diagnostic methods, taking into account the limitations of currently available tools. Conclusions. When planning future studies, it is important to determine whether children's understanding or production of humor will be assessed in order to select diagnostic instruments, given the complex structure of the children's humor construct and its age-specific characteristics, as well as the limitations of the methods used.